Modified attapulgite-based diaphragm as well as preparation method and application thereof

By modifying the combination of concave and concave rock stone, pore-forming agent and binder, a separator with rich pore structure is formed, which solves the deformation and shrinkage of the lithium-ion battery separator under external forces, lithium dendrites puncture and high temperature, and achieves better mechanical properties and thermal stability.

CN119627360AActive Publication Date: 2025-03-14CHINA UNIV OF MINING & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411816644.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are susceptible to external forces and puncture of lithium dendrites during assembly, causing mechanical deformation, and shrink when heated, affecting the safety of the battery.

Method used

By pickling or chemically modifying the concave and concave rock stone and mixing it thoroughly with the pore-forming agent and the binder, a modified concave rock stone-based separator is formed. Through the film formation and pore formation process, the diaphragm forms a rich pore structure, improves porosity and liquid absorption, and enhances mechanical properties and thermal stability.

Benefits of technology

The modified concave and concave rock-based separator remains stable at high temperatures, avoiding heat shrinkage, and enhancing the safety and electrochemical properties of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627360A_ABST
    Figure CN119627360A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a modified attapulgite-based diaphragm as well as a preparation method and application thereof, and the preparation method comprises the following steps: carrying out acid pickling modification or chemical modification on attapulgite to obtain modified attapulgite; mixing the modified attapulgite with the solution A to obtain a mixture B, wherein the solution A comprises a pore-forming agent; mixing the mixture B with a binder to obtain mixed slurry C; coating a substrate with the mixed slurry C, soaking the substrate coated with the slurry into water to form a film and pores, and drying after film formation to obtain the modified attapulgite-based diaphragm; the obtained modified attapulgite-based diaphragm has good mechanical properties and thermal stability, and avoids mechanical deformation caused by external force and piercing of lithium dendrites and shrinkage caused by heating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery material technology, and more specifically, to a modified attapulgite-based diaphragm and a preparation method and application thereof. Background Art

[0002] With the depletion of fossil fuels and the increasingly serious environmental pollution caused by the burning of fossil fuels, the development of renewable clean energy such as wind energy, hydropower, solar energy and tidal energy has become a research hotspot. However, these clean energy sources have limitations and fluctuations in time and space, making them difficult to apply on a large scale. The emergence of new energy storage devices such as lithium-ion batteries and supercapacitors has provided a breakthrough in solving this problem and ushered in an excellent development opportunity. Lithium-ion batteries are widely used in electric vehicles, digital devices and other fields due to their high energy density and other advantages, and have great development prospects.

[0003] Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, separator and electrolyte. The performance of the separator not only affects the electrochemical performance of the battery, but also has an important impact on the safety of the battery. The separator has two main functions in the battery. One is to prevent the positive and negative electrode materials from directly contacting and short-circuiting to cause safety accidents, and the other is to provide a channel for the diffusion and transmission of lithium ions between the positive and negative electrodes. Due to the existing problems of "lithium dendrites", thermal runaway, spontaneous combustion, etc. in lithium batteries, higher requirements are placed on the thermal stability and mechanical properties of the separator, which can avoid safety accidents caused by deformation caused by external forces during assembly, piercing of lithium dendrites, and shrinkage when heated, thereby ensuring safety. Summary of the invention

[0004] The present application is provided to solve the above defects existing in the prior art. A modified attapulgite-based diaphragm and its preparation method and application are needed to solve the problems of mechanical deformation of the diaphragm due to external force and piercing of lithium dendrites during assembly, and shrinkage due to heat.

[0005] In the first aspect of the present application, a method for preparing a modified attapulgite-based diaphragm is provided, the preparation method comprising: acid-washing or chemically modifying attapulgite to obtain modified attapulgite; mixing the modified attapulgite and solution A to obtain a mixture B, wherein the solution A includes a pore-forming agent; mixing the mixture B and a binder to obtain a mixed slurry C; coating the mixed slurry C on a substrate, and immersing the substrate coated with the slurry in water to form a film and form pores, and drying the film after formation to obtain a modified attapulgite-based diaphragm.

[0006] In a second aspect of the present application, there is provided a modified attapulgite-based diaphragm prepared by the preparation method described in any embodiment of the present application.

[0007] The third aspect of the present application provides an application of the modified attapulgite-based diaphragm described in any embodiment of the present application in a battery.

[0008] The modified attapulgite-based diaphragm and its preparation method and application provided in each embodiment of the present application are that the attapulgite itself has a rich pore structure. The attapulgite is first modified and then fully mixed with a pore-forming agent and a binder to obtain a slurry, and the slurry is coated to form a film; the coated film is immersed in water, and after a phase conversion process, the obtained diaphragm has a rich pore structure, which can improve the porosity and liquid absorption rate of the diaphragm, and at the same time provide a convenient channel for the rapid transmission of lithium ions. On the basis of the good performance of attapulgite, a diaphragm with good mechanical properties and thermal stability is obtained through the process of film formation and pore formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.

[0010] Figure 1 The thermal stability diagram of the modified attapulgite-based diaphragm prepared according to different embodiments of the present application is shown; Figure 2 The scanning electron microscope image of the modified attapulgite-based diaphragm prepared according to Example 1 of the present application is shown; Figure 3 The LSV curves of the modified attapulgite-based separators prepared according to different embodiments of the present application and the commercial PP separators are shown. DETAILED DESCRIPTION

[0011] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation methods. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation methods, but are not intended to limit the present application.

[0012] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0013] According to an embodiment of the present application, a method for preparing a modified attapulgite-based diaphragm is provided, the preparation method comprising: acid-washing or chemically modifying attapulgite to obtain modified attapulgite; mixing the modified attapulgite and solution A to obtain a mixture B, wherein the solution A includes a pore-forming agent; mixing the mixture B and a binder to obtain a mixed slurry C; coating the mixed slurry C on a substrate, and immersing the substrate coated with the slurry in water to form a film and form pores, and drying after film formation to obtain a modified attapulgite-based diaphragm.

[0014] This application selects attapulgite as the raw material of the diaphragm. Attapulgite is a natural mineral with a developed pore structure, which makes the diaphragm have high porosity, electrolyte absorption rate and ion conductivity, further ensuring the high specific capacity and high rate performance of the battery; secondly, natural minerals have excellent thermal stability and mechanical properties, which can give the diaphragm thermal stability and mechanical properties, avoid shrinkage of the diaphragm when heated, and prevent mechanical deformation when lithium dendrites pierce and external forces occur.

[0015] In the present application, the attapulgite is acid-modified or chemically modified. On the one hand, the acid-modification can etch a large number of nanoscale channels inside the attapulgite, thereby improving the overall porosity and liquid absorption rate of the diaphragm; on the other hand, the chemical modification can selectively graft different functional patterns on the surface of the attapulgite, thereby achieving a strong interaction force between the chemically modified attapulgite and the binder, further significantly enhancing the overall stability of the diaphragm.

[0016] After the attapulgite is mixed with the pore-forming agent and the binder, a membrane is first formed, and then pores are formed in water. In this way, through the phase conversion process, the modified attapulgite in the modified attapulgite membrane can be tightly bonded, and a uniform pore structure with a suitable pore size can be formed on the attapulgite membrane, and the pore structure distribution is relatively dense. In this way, the modified attapulgite membrane as a whole can have good mechanical properties and thermal stability. The modified attapulgite-based membrane obtained in the present application did not shrink and deform at 160°C, and only slightly deformed at 180°C.

[0017] In some embodiments, the acid-washing modification includes: mixing the attapulgite and an acid solution and then heating the mixture to obtain modified attapulgite.

[0018] In some embodiments, the acid solution is an inorganic acid solution, including one of hydrochloric acid, sulfuric acid and nitric acid; the heating conditions for pickling modification include: temperature of 65-80°C and time of 2-5 hours. By modifying the attapulgite under these conditions, a better modification effect can be obtained.

[0019] In some embodiments, the acid-washed and modified product is centrifuged, and the attapulgite obtained by centrifugation is washed and then dried at a drying temperature of 100-120°C.

[0020] In some embodiments, the chemical modification comprises: mixing attapulgite, a modifier and a mixed solution D, and obtaining modified attapulgite after heating, wherein the mixed solution D comprises glacial acetic acid, ethanol and water. The modified attapulgite membrane obtained after chemical modification has a better liquid absorption rate than the modified attapulgite membrane obtained after acid modification.

[0021] In some embodiments, the modifier is one of γ-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560), polymethyl methacrylate (PMMA), hexadecyltrimethylammonium bromide (CTAB), etc.; the heating conditions for chemical modification include: temperature of 65-85 ° C, time of 3-8 h.

[0022] In some embodiments, the pore-forming agent is one or more of polyvinyl pyrrolidone (PVP), dimethylacetamide (DMAc), polyethylene glycol (PEG), etc. In some embodiments, the organic solvent of solution A is one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), acetone (ACE), chloroform (TCM), etc. In some embodiments, the process of mixing the pore-forming agent and the organic solvent to obtain solution A is room temperature. And stirring is performed. In some embodiments, ultrasonic dispersion treatment is performed during the process of mixing the modified attapulgite and solution A to obtain mixture B, and the time of ultrasonic dispersion is 1-3 h, and the temperature of ultrasonic dispersion is room temperature. To improve the effect of mixing uniformity.

[0023] In some embodiments, the mixed slurry C obtained by mixing the mixture B and the binder is subjected to a heating treatment; the conditions for the heating treatment of the mixed slurry C include a temperature of 50-70° C. and a time of 12-30 h.

[0024] In some embodiments, the binder is one or more of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA) or polyvinylidene fluoride (PVDF), etc. The modified attapulgite and the binder are combined to obtain a diaphragm that can be used in a battery, so that the diaphragm has good porosity, thermal stability and mechanical properties.

[0025] In some embodiments, the mass ratio of attapulgite to pore former is 5-7: 1. In some embodiments, the mass ratio of modified attapulgite to binder is 0.1-0.5: 1. Preferably, the mass ratio of modified attapulgite to binder is 0.2-0.3:1.

[0026] In some embodiments, coating the mixed slurry C on the substrate includes: coating the mixed slurry C on the substrate using a coating machine. The substrate may include a glass plate, etc. Further, the height between the coating machine and the substrate is 150-250 μm.

[0027] In some embodiments, the time for forming a film and holes by immersing the substrate coated with the slurry in water is 24-48 hours. In some embodiments, when the substrate coated with the slurry is immersed in water to form a film, the temperature of the water is room temperature.

[0028] In some embodiments, freeze drying is performed after film formation, and the minimum freeze drying temperature is -65°C and the time is 30-40 hours.

[0029] According to an embodiment of the present application, there is also provided a modified attapulgite-based diaphragm prepared by the preparation method described in any embodiment of the present application.

[0030] In some embodiments, the modified attapulgite-based separator has a thickness of 80-90 μm.

[0031] According to an embodiment of the present application, there is also provided an application of the modified attapulgite-based diaphragm described in any embodiment of the present application in a battery.

[0032] According to an embodiment of the present application, a battery is also provided, the battery comprising the modified attapulgite-based separator described in any embodiment of the present application. Further, the battery also comprises a positive electrode, a negative electrode, and the like.

[0033] Example 1 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of acid-washed attapulgite: take 6 g of attapulgite and add it into a beaker, add 55 ml of deionized water and 5 ml of 37% concentrated hydrochloric acid successively, stir the hydrochloric acid solution and attapulgite in a 75°C oil bath for acid washing for 4 h; centrifuge and wash, and dry at 110°C to obtain the acid-washed attapulgite.

[0034] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.1 g of acid-washed attapulgite to solution A, and ultrasonically dispersing the mixture at room temperature for 1 h to obtain a mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0035] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (HATP0.1) prepared by the method of Example 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0036] The scanning electron microscopy image of the modified attapulgite-based diaphragm (HATP0.1) is shown in Figure 2 As shown. Figure 2 Scanning electron microscope images show that attapulgite is evenly distributed in the diaphragm, which can significantly enhance the mechanical properties and thermal stability of the heat-resistant modified attapulgite-based diaphragm; at the same time, the dissolution of solvents and pore-forming agents produces a rich pore structure, which not only improves the liquid absorption rate of the diaphragm, but also provides a convenient channel for the rapid transmission of lithium ions.

[0037] The prepared heat-resistant modified attapulgite-based diaphragm is assembled into a half-cell: the assembly order of the half-cell is as follows: positive electrode shell, spring, gasket, positive electrode sheet, diaphragm, lithium sheet, negative electrode shell. The positive electrode is lithium iron phosphate (LiFePO4), the positive electrode sheet diameter is 10 mm, the diaphragm is the prepared heat-resistant modified attapulgite-based diaphragm, and the diaphragm diameter is 19 mm; the electrolyte is 1 M LiPF6. Figure 3 The LSV curve of the modified attapulgite-based diaphragm (Example 1-8) is still stable at a voltage of 4.5 V. Example 2 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of acid-washed attapulgite: take 6 g of attapulgite and add it into a beaker, add 55 ml of deionized water and 5 ml of 37% concentrated hydrochloric acid successively, stir the hydrochloric acid solution and attapulgite in a 75°C oil bath for acid washing for 4 h; centrifuge and wash, and dry at 110°C to obtain the acid-washed attapulgite.

[0038] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.2 g of acid-washed attapulgite to solution A, and ultrasonically dispersing the mixture at room temperature for 1 h to obtain a mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0039] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (HATP0.2) prepared by the method of Example 2 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0040] Example 3 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of acid-washed attapulgite: take 6 g of attapulgite and add it into a beaker, add 55 ml of deionized water and 5 ml of 37% concentrated hydrochloric acid successively, stir the hydrochloric acid solution and attapulgite in a 75°C oil bath for acid washing for 4 h; centrifuge and wash, and dry at 110°C to obtain the acid-washed attapulgite.

[0041] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.3 g of acid-washed attapulgite to solution A, and ultrasonically dispersing the mixture at room temperature for 1 h to obtain a mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0042] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (HATP0.3) prepared by the method of Example 3 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0043] Example 4 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of acid-washed attapulgite: take 6 g of attapulgite and add it into a beaker, add 55 ml of deionized water and 5 ml of 37% concentrated hydrochloric acid successively, stir the hydrochloric acid solution and attapulgite in a 75°C oil bath for acid washing for 4 h; centrifuge and wash, and dry at 110°C to obtain the acid-washed attapulgite.

[0044] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.4 g of acid-washed attapulgite to solution A, and ultrasonically dispersing the mixture at room temperature for 1 h to obtain a mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0045] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (HATP0.4) prepared by the method of Example 4 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0046] Example 5 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of chemically modified attapulgite: dilute glacial acetic acid with deionized water to a glacial acetic acid solution with a pH of 3, add 50 ml of anhydrous ethanol to 100 ml of the glacial acetic acid solution, then add 10 g of attapulgite and 0.3 g of a silane coupling agent (KH-550) to the mixed solution, stir in an oil bath at 70 ° C for 6 h; centrifuge and wash, and dry at 110 ° C to obtain chemically modified attapulgite.

[0047] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.1 g of modified attapulgite to solution A, and dispersing by ultrasonic at room temperature for 1 h to obtain mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0048] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (MATP0.1) prepared by the method of Example 5 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0049] Example 6 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of chemically modified attapulgite: dilute glacial acetic acid with deionized water to a glacial acetic acid solution with a pH of 3, add 50 ml of anhydrous ethanol to 100 ml of the glacial acetic acid solution, then add 10 g of attapulgite and 0.3 g of a silane coupling agent (KH-550) to the mixed solution, stir in an oil bath at 70 ° C for 6 h; centrifuge and wash, and dry at 110 ° C to obtain chemically modified attapulgite.

[0050] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.2 g of modified attapulgite to solution A, and dispersing by ultrasonic at room temperature for 1 h to obtain mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0051] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (MATP0.2) prepared by the method of Example 6 is as follows: Figure 1 As shown. Figure 1It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0052] Example 7 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of chemically modified attapulgite: dilute glacial acetic acid with deionized water to a glacial acetic acid solution with a pH of 3, add 50 ml of anhydrous ethanol to 100 ml of the glacial acetic acid solution, then add 10 g of attapulgite and 0.3 g of a silane coupling agent (KH-550) to the mixed solution, stir in an oil bath at 70 ° C for 6 h; centrifuge and wash, and dry at 110 ° C to obtain chemically modified attapulgite.

[0053] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.3 g of modified attapulgite to solution A, and ultrasonically dispersing the mixture at room temperature for 1 h to obtain a mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0054] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (MATP0.3) prepared by the method of Example 7 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0055] Example 8 This embodiment relates to a method for preparing a heat-resistant modified attapulgite-based diaphragm, comprising the following steps: Step (1), preparation step of chemically modified attapulgite: dilute glacial acetic acid with deionized water to a glacial acetic acid solution with a pH of 3, add 50 ml of anhydrous ethanol to 100 ml of the glacial acetic acid solution, then add 10 g of attapulgite and 0.3 g of a silane coupling agent (KH-550) to the mixed solution, stir in an oil bath at 70 ° C for 6 h; centrifuge and wash, and dry at 110 ° C to obtain chemically modified attapulgite.

[0056] Step (2), add 1.0 g of pore-forming agent polyvinyl pyrrolidone to 9.5 ml of organic solvent N,N-dimethylformamide (DMF), and stir at room temperature for 0.5 h until the pore-forming agent is completely dissolved to obtain solution A. Step (3), adding 0.4 g of modified attapulgite to solution A, and dispersing by ultrasonic at room temperature for 1 h to obtain mixture B; Step (4), adding 1.0 g of a binder polyvinylidene fluoride (PVDF) to the mixture B, stirring in an oil bath at 50° C. for 12 h, to obtain a mixed slurry C; Step (5), placing the mixed slurry C on a glass plate, and using a scraper (height selected to be 250 µm) to evenly coat the slurry on the glass plate; Step (6), immersing the glass plate coated with the slurry into deionized water to achieve phase conversion and film formation, the depth of the deionized water is 1 cm above the glass plate, the water temperature is room temperature, and the immersion time is 24 h; Step (7), placing the film-forming sample in a freeze drying oven, wherein the minimum freeze drying temperature is -65°C and the time is 36 hours.

[0057] The thermal stability test of the heat-resistant modified attapulgite-based diaphragm (MATP0.4) prepared by the method involved in Example 8 is as follows: Figure 1 As shown. Figure 1 It can be seen that the prepared heat-resistant modified attapulgite-based diaphragm did not shrink at 160 °C, while the commercial PP diaphragm shrank significantly at 160 °C; when the temperature continued to rise to 180 °C, the commercial PP diaphragm shrank severely, while the prepared heat-resistant modified attapulgite-based diaphragm only shrank slightly.

[0058] The commercial PP diaphragm and the heat-resistant modified attapulgite-based diaphragm in Examples 1 to 8 were subjected to performance tests, and the test data are shown in Table 1.

[0059] Table 1 Battery separator performance of various examples Through the performance of the modified attapulgite-based diaphragm of Examples 1 to 8, it can be obtained that the modified attapulgite-based diaphragm has a relatively consistent thickness, a porosity greater than 50%, and a liquid absorption rate greater than 500%. Therefore, as a diaphragm for a lithium battery, it can enable the lithium battery to exert better electrochemical performance. The modified attapulgite-based diaphragm obtained in each example has a heat shrinkage rate of 0% at 160°C, has good safety performance, and avoids safety accidents at higher temperatures.

[0060] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.

[0061] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.

[0062] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified attapulgite-based diaphragm, characterized in that: The preparation method comprises: acid-washing or chemically modifying attapulgite to obtain modified attapulgite; mixing the modified attapulgite with a solution A to obtain a mixture B, wherein the solution A comprises a pore-forming agent; mixing the mixture B with a binder to obtain a mixed slurry C; coating the mixed slurry C on a substrate, and immersing the substrate coated with the slurry in water to form a film and form pores, and drying after the film is formed to obtain a modified attapulgite-based diaphragm.

2. The preparation method according to claim 1, characterized in that: The acid-washing modification comprises: mixing the attapulgite with an acid solution and then heating the mixture to obtain modified attapulgite.

3. The preparation method according to claim 2, characterized in that The acid solution is an inorganic acid solution, including one of hydrochloric acid, sulfuric acid and nitric acid; the heating conditions for pickling modification include: temperature of 65-80°C and time of 2-5 hours.

4. The preparation method according to claim 1, characterized in that: The chemical modification comprises: mixing attapulgite, a modifier and a mixed solution D, and heating the mixture to obtain the modified attapulgite, wherein the mixed solution D comprises glacial acetic acid, ethanol and water.

5. The preparation method according to claim 4, characterized in that The modifier is one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, polymethyl methacrylate, and hexadecyltrimethylammonium bromide; the heating conditions for chemical modification include: temperature of 65-85° C. and time of 3-8 h.

6. The preparation method according to claim 1, characterized in that: The pore-forming agent is one or more of polyvinyl pyrrolidone, dimethylacetamide and polyethylene glycol.

7. The preparation method according to claim 1, characterized in that The mixed slurry C obtained by mixing the mixture B and the binder is subjected to a heating treatment; the conditions for the heating treatment of the mixed slurry C include a temperature of 50-70° C. and a time of 12-30 hours; and the binder is polyvinylidene fluoride.

8. The preparation method according to claim 1, characterized in that The time for film formation and pore formation is 24-48 h when the substrate coated with the slurry is immersed in water.

9. The modified attapulgite-based diaphragm prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the modified attapulgite-based separator according to claim 9 in batteries.

Citation Information

Patent Citations

  • Preparation method of organic modified attapulgite blended ceramic particle coating commercially available polyolefin diaphragm

    CN110157029A